2019
DOI: 10.1007/s00256-019-03266-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MRI of the wrist in less than 20 seconds: normal midcarpal motion and reader reliability

Abstract: OBJECTIVE-To describe the normal motion pattern at the midcarpal compartment during active radial-ulnar deviation of the wrist using dynamic MRI and to determine the observer performance for measurements obtained in asymptomatic volunteers.METHODS-Dynamic MRI of 35 wrists in 19 asymptomatic volunteers (age mean 30.4 yrs, sd 8.6) was performed during active radial-ulnar deviation using a fast gradient-echo pulse sequence with 315 ms temporal resolution (acquisition time, 19 sec). Two independent readers measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Beyond its utility in dynamic speech imaging, the proposed data-sampling and reconstruction method may benefit other applications, particularly those in which dynamic edge information is critical, such as (1) dynamic MRI of cardiac function, [39][40][41] in which the endocardial and epicardial contours are of greatest importance; (2) dynamic MRI of the upper and lower airway, 42,43 where the pharyngeal airway and trachea are most critical; and (3) dynamic MRI of joint motion, 44,45 where the movement of bones and cartilage are most critical. The proposed sampling strategy may also benefit a 3D stack-of-radial (a.k.a.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its utility in dynamic speech imaging, the proposed data-sampling and reconstruction method may benefit other applications, particularly those in which dynamic edge information is critical, such as (1) dynamic MRI of cardiac function, [39][40][41] in which the endocardial and epicardial contours are of greatest importance; (2) dynamic MRI of the upper and lower airway, 42,43 where the pharyngeal airway and trachea are most critical; and (3) dynamic MRI of joint motion, 44,45 where the movement of bones and cartilage are most critical. The proposed sampling strategy may also benefit a 3D stack-of-radial (a.k.a.…”
Section: Discussionmentioning
confidence: 99%
“…Three gradient echo sequences typically available on MRI scanners are suitable for real-time dynamic MRI and have already been used in previous studies to understand in vivo joint biomechanics. These are balanced steady-state free precession (SSFP) sequence [26,[28][29][30][31][32][33], RF-spoiled sequence [29,[34][35][36], and ultrafast gradient echo (UFGE) sequence [5,37], with different acronyms used by each MRI scanner manufacturer (Table 1).…”
Section: Real-time Dynamic Mri Sequences and Parametersmentioning
confidence: 99%
“…Cartesian and radial sampling of the k-space were both used for real-time dynamic MRI. Radial sampling was particularly suitable for real-time RF-spoiled sequences at 3.0 T [29,35], allowing an increase in temporal resolution without image quality deterioration with the use of constrained iterative reconstruction [29]. Such iterative reconstruction of real-time images often requires the addition of graphic processing units to the current MRI systems [45,46].…”
Section: Real-time Dynamic Mri Sequences and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, standard MRI evaluates the stationary, immobilized wrist and is unable to directly evaluate dynamic carpal instability. Only a few studies have reported the use of fast MRI acquisition to visualize carpal kinematics[11, 16, 17]. This is primarily due to the slow encoding of k-space inherent to MRI that results in low temporal resolution, and the presence of susceptibility and other artifacts that may compromise image quality[11].…”
Section: Introductionmentioning
confidence: 99%